1984
DOI: 10.1042/cs0660569
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Study of Cation Transport in vivo: Effects of Digoxin Administration and of Chronic Renal Failure on the Disposition of An Oral Load of Rubidium Chloride

Abstract: In order to study cation transport in vivo we have measured the changes in plasma and intra-erythrocytic rubidium concentrations following an oral load of rubidium chloride. The changes in plasma rubidium concentration are related to the distribution of rubidium to all the body tissues and the changes in intra-erythrocytic rubidium concentrations provide an example of rubidium uptake by one particular tissue. In eight healthy volunteers pretreatment with a loading dose of digoxin (20 micrograms/kg) enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The changes in plasma rubidium concentrations reflect the overall transport of rubidium out of the plasma into the intracellular compartment, whilst the changes in intra-erythrocytic rubidium concentrations reflect transport into a single cellular compartment, which may or may not be representative of the intracellular compartment as a whole. We have previously shown that the disposition of rubidium is altered in healthy volunteers who have taken a loading dose of digoxin (Boon et al, 1984b), and in this study we have found similar changes in patients who have been taking digoxin in maintenance dosage for less than 10 days. These alterations are in a direction which is consistent with a generalized reduction in the activity of the Na+,K+-ATPase.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The changes in plasma rubidium concentrations reflect the overall transport of rubidium out of the plasma into the intracellular compartment, whilst the changes in intra-erythrocytic rubidium concentrations reflect transport into a single cellular compartment, which may or may not be representative of the intracellular compartment as a whole. We have previously shown that the disposition of rubidium is altered in healthy volunteers who have taken a loading dose of digoxin (Boon et al, 1984b), and in this study we have found similar changes in patients who have been taking digoxin in maintenance dosage for less than 10 days. These alterations are in a direction which is consistent with a generalized reduction in the activity of the Na+,K+-ATPase.…”
Section: Discussionsupporting
confidence: 73%
“…We have previously shown that the disposition of rubidium is altered in healthy volunteers who have taken a loading dose of digoxin (Boon et al, 1984b), and in this study we have found similar changes in patients who have been taking digoxin in maintenance dosage for less than 10 days. These alterations are in a direction which is consistent with a generalized reduction in the activity of the Na+,K+-ATPase.…”
Section: Short-term Digoxinsupporting
confidence: 80%
See 1 more Smart Citation
“…Using thlese in vitro techniques, several groups have demonstrated changes in Na+,K+-ATPase activity in both depression and mania (Naylor et al, 1973(Naylor et al, , 1976Hokin-lVeaverson et al, 1974;Hesketh et al, 1977~) and following the administration of lithium salts to both patients (Naylor et al, 1974;Hokin-Neaverson et al, 1976;Hesketh et al, 1978;Johnston et al, 1980) and healthy volunteers (Naylor et al, 1977). These studies have been extended recently in our own work, using an oral load of nonradioisotopic rubidium to assess cation transport in vivo in affective illness and following the administration of lithium (Boon et al, 1984;Wood et al, 1987aJ).…”
mentioning
confidence: 83%
“…Such functional changes have been demonstrated clinically during the administration of digoxin, a Na+,K+-ATPase inhibitor. Abnormalities of pump function in peripheral tissues have been reported in disease states, including hypertension (Wambach et al, 1980), and chranic renal failure (Boon et al, 1984). Others have reported abnormalities of the Na+,K+-ATPase in affective illness and in relation to treatment of patients suffering from either unipolar or bipolar affective illness.…”
Section: Na+ K+-atpasementioning
confidence: 99%